Gambaran Pola Makan Pada Anak Usia Sekolah di SDN Pondok Kelapa 06 Jakarta Timur - Azizah, Restiana Nur; Rizana, Anna (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRAK Children's diet really needs serious treatment because it affects the optimal status of growth, development, and brain intelligence for children. During the growth period and feeding needs to be regulated according to the recommended nutritional adequacy rate. Children who lack daily physical activity can cause their bodies to expend less energy. One of the keys to fulfilling children's nutritional needs is to introduce them to various types of food. If a child is too picky about food (picky eater) then the child will be at risk of experiencing nutritional deficiencies. A healthy diet to support children's growth and development must be given varied intake from an early age, pay attention to food hygiene, and be in accordance with the child's physical activity so that the child's ideal weight is achieved. Eating habits is a term used to describe habits and behaviors related to dietary regulation. This type of stimulating food needs to be considered so as not to damage the gastric mucosal lining. To know if there is an overview of eating patterns in elementary school-age children. This study uses an observational method with a quantitative analytic approach with a cross sectional study design that aims to analyze the risk factors and effects at the same time. Where the measurement of the variable that is examined is the description of eating patterns in elementary school-age children. Based on the results of filling out the questionnaire conducted by students in grades IV and V at Pondok Kelapa 06 Sdn, East Jakarta, from all 60 respondents, the results obtained were the gender (demographic data) of 38 female respondents (63.33%) and 22 male respondents (36.37%). From the results of the univariate analysis, it was found that out of the 60 respondents who were examined, there were 45 respondents (75%) who had a good diet and 15 people (25%) who had a bad diet. There is an overview of eating patterns in children at Pondok Kelapa 06 Sdn. A description of the types of food that are often consumed by school-age children at Pondok Kelapa 06 elementary school, East Jakarta who consume carbohydrate sources such as rice as many as 38 people (64%) and noodles as many as 40 people (67%) , who consumed animal side dishes such as chicken eggs as many as 43 people (72%), who consumed vegetable side dishes such as tofu as many as 43 people (72%), who consumed vegetables such as carrots, bean sprouts and cucumbers as many as 23 people (38%) and those who consumed fruit like watermelon as many as 29 people (48%). Researchers provide advice to all students of Pondok Kelapa 06 Elementary School to pay more attention to eating patterns, eating habits and types of food that are healthy and clean. Because a good diet is expected to avoid the risk of malnutrition or other diseases that can affect the growth and development of school-age children. a. Education about healthy snacks Provide education to elementary school-age children about the criteria for snacks that are healthy and safe for health by providing open pockets or leaflets showing the characteristics of unhealthy foods in terms of color, shape, aroma and texture. b. Education about balanced nutrition Providing education about balanced nutrition through pictorial media such as "Tumpeng Nutrition Balanced" and "10 Messages of Balanced Nutrition". Keywords: Description, Eating Patterns and Types of Food in School-Aged Children  ABSTRAK Pola makan anak sangat diperlukan penanganan yang serius karena hal ini mempengaruhi status pertumbuhan, perkembangan, dan kecerdasan otak yang optimal untuk anak. Selama dalam masa pertumbuhan dan pemberian makanan perlu diatur sesuai dengan angka kecukupan gizi yang dianjurkan. Anak-anak yang kurang melakukan aktivitas fisik sehari - hari dapat menyebabkan tubuhnya kurang mengeluarkan energi. Salah satu kunci agar kebutuhan nutrisi pada anak terpenuhi yaitu mengenalkannya dengan berbagai jenis makanan. Jika anak terlalu memilih-milih makanan (picky eater) maka anak tersebut akan beresiko mengalami kekurangan nutrisi. Pola makan yang sehat untuk mendukung tumbuh kembang anak harus diberikan asupan yang bervariasi sejak dini, memperhatikan kebersihan makanan, dan sesuai dengan aktivitas fisik anak agar tercapai berat badan anak yang ideal. Kebiasaan makan merupakan istilah yang digunakan untuk menggambarkan kebiasaan dan perilaku yang berhubungan dengan pengaturan pola makan. Jenis makanan merangsang perlu di perhatikan agar tidak merusak lapisan mukosa lambung. Untuk mengetahui adanya gambaran pola makan pada anak usia sekolah dasar. Penelitian ini menggunakan metode observasional dengan pendekatan kuantitatif analitik dengan desain studi cross sectional yang bertujuan untuk menganalisa faktor resiko serta efek dalam waktu yang bersama-sama. Dimana pengukuran variabe yang di teliti yaitu gambaran pola makan pada anak usia sekolah dasar. Berdasarkan hasil pengisian kuesioner yang dilakukan oleh pelajar kelas IV dan V di Sdn Pondok Kelapa 06 Jakarta Timur dari seluruh responden yang berjumlah 60 responden di dapatkan hasil jenis kelamin (data demografi) responden perempuan sebanyak 38 orang (63,33%) dan responden laki-laki sebanyak 22 orang (36,37%). Dari hasil analisis univariat didapatkan data bahwa dari 60 responden yang di teliti terdapat responden yang memiliki pola makan baik sebanyak 45 orang (75%) dan yang memiliki pola makan buruk sebanyak 15 orang (25%). Adanya gambaran pola makan pada anak Sdn pondok kelapa 06. Gambaran jenis makanan yang sering dikonsumsi pada anak usia sekolah di sdn pondok kelapa 06 Jakarta Timur yang mengkonsumsi sumber karbohidrat seperti nasi sebanyak 38 orang (64%) dan mie sebanyak 40 orang (67%), yang mengkonsumsi lauk hewani seperti telur ayam sebanyak 43 orang (72%), yang mengkonsumsi lauk nabati seperti tahu sebanyak 43 orang (72%), yang mengkonsumsi sayuran seperti wortel, tauge dan mentimun sebanyak 23 orang (38%) serta yang mengkonsumsi buah seperti buah semangka sebanyak 29 orang (48%).  Peneliti memberikan saran bagi seluruh siswa dan siswi SDN Pondok Kelapa 06 agar lebih memperhatikan pola makan, kebiasaan makan dan jenis makanan yang sehat dan bersih. Karena dengan pola makan yang baik diharapkan dapat terhindar dari resiko terkena gizi buruk atau penyakit lainnya yang bisa mempengaruhi pertumbuhan dan perkembangan pada anak usia sekolah. a. Edukasi tentang makanan jajanan yang sehat Memberikan edukasi kepada anak usia sekolah dasar tentang kriteria makanan jajanan yang sehat dan aman untuk kesehatan dengan memberikan buka saku atau leaflet ciri-ciri makanan yang tidak sehat baik dari segi warna, bentuk, aroma dan tekstur. b. Edukasi tentang gizi seimbang Memberikan edukasi tentang gizi seimbang melalui media bergambar seperti “Tumpeng Gizi Seimbang” dan “10 Pesan Gizi Seimbang”. Kata Kunci: Gambaran, Pola Makan dan Jenis Makanan Pada Anak Usia Sekolah.